The Internalisation of the Spiritual Values of Surah Al-Fātiḥah in Islamic Character Education: A Tafsīr Study and Conceptual Analysis. - kholil kholil; Lukman Hakim; Achmad Izzul Hisyam; Handri Hartanto; Benny Prasetya (Al-Hikmah: International Journal of Islamic Studies, 2026)
Contemporary education is increasingly dominated by instrumental rationality that prioritizes cognitive performance, efficiency, and competitiveness, often marginalizing learners’ moral and spiritual development. Within Islamic education, this tendency generates epistemological and ethical challenges manifested in value disorientation, weakened moral integrity, and fragile character formation. This study aims to formulate a conceptual model for the internalization of the spiritual values of Surah Al-Fatihah as the foundation of Islamic character education. Employing a qualitative library-based approach with a conceptual-analytical orientation, the study draws on authoritative classical Qur’anic exegesis as primary sources and contemporary Islamic educational literature as supporting references. Data are analyzed through systematic content analysis encompassing descriptive, interpretative, and applicative-synthetic stages, guided by the double movement approach to ensure contextual relevance while preserving normative substance. The findings reveal that Surah Al-Fatihah embodies a fundamental, hierarchical, and integrative structure of spiritual values, including tawhid, ‘ubudiyyah, rahmah, gratitude, guidance, and eschatological accountability. These values are mapped into three interrelated dimensions of Islamic character education spiritual orientation (ta’alluq billah), moral disposition (akhlaqiyyah), and social responsibility (insaniyyah) and synthesized into a conceptual model linking educational aims, learning content, pedagogical strategies, institutional culture, and character assessment. Overall, the study positions Surah Al-Fatihah as an epistemological and pedagogical foundation for ta’dib-oriented Islamic character education in addressing contemporary moral and spiritual challenges.